KEBIJAKAN PEMERINTAH DAERAH DALAM PENGATURAN SUMBER PENDAPATAN ASLI DAERAH DALAM KERANGKA OTONOMI DAERAH (STUDI PADA KABUPATEN NIAS BARAT) - Agnes Gulo; Muhammad Abduh; Pendastaren Tarigan; Faisal Akbar Nasution (USU LAW JOURNAL, 2013)
West Nias Regency as a new autonomous regions is required to issue a policy in the regulation of local revenue sources that are not entirely dependent on central government funding. In this study, there are several issues to be discussed include the formulation of regulation of financial resources within the framework of the general areas of regional autonomy, policy and policy implementation has been done by the Government of West Nias, the obstacles faced by the Government of West Nias Regency. The regulation of financial resources especially regional revenue has been established to provide broad authority to local goverments to levy local taxes and retribution, the policy of goverment west nias regency explore potential revenue has been estabished by means of issue a local regulation although not all of these legal products formed. The Policy of Government West Nias in running facing external and internal obstacles.